Negotiating identity and survival: the Chinese Indonesians’ journey in the last century - Wang, Li Wei Giovanni (Nanyang Technological University, 2024)
This paper aims to examine the history and socio-cultural development of Indonesian Chinese, known colloquially as Chinese Indonesians, from 1965 to 1998 during the Suharto era. Existing scholarship on this subject often adopts a macro perspective when examining this period of history, with the discourse heavily anchored on the political aspects, causally portraying Indonesian Chinese as victims of discrimination who were passive and powerless. By doing so, it undermines the historical influence and agency of Indonesian Chinese in the process. Nevertheless, this paper aims to shed light on how Chinese Indonesians negotiate their identity and reconcile their dual identity as “Chinese Indonesians” in the face of adversity.